PENGARUH KUALITAS PELAYANAN, PENGETAHUAN KONSUMEN, DAN PERIKLANAN TERHADAP MINAT MENABUNG DI BANK JATIM KCP UNTAG SEMOLOWARU SURABAYA - Niki Mafatzi, Noval; Rahmiyati, Nekky (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study examines the influence of service quality, consumer knowledge, and advertising on saving interest at Bank Jatim KCP Untag Semolowaru Surabaya. The stagnation in the growth of new savings accounts, despite the bank’s strategic location within an academic environment, raises questions about the effectiveness of its service delivery and marketing strategies. Using a quantitative approach, data were collected from 100 respondents through structured questionnaires and analyzed using multiple linear regression with SPSS version 30. The findings indicate that service quality, consumer knowledge, and advertising significantly affect saving interest both partially and simultaneously. Among the three variables, service quality has the most dominant influence. The study suggests that improving service experiences, enhancing financial literacy, and optimizing digital advertising strategies are essential to increase saving behavior, particularly among younger, tech-savvy consumers. These insights offer strategic implications for banks operating in competitive and digitally evolving environments.